Reforma en salud: complejidad y límites de la formación de recursos humanos especializados - Mendoza-Arana, Pedro Jesús (2018)
We explore the Health Sector Reform process form a systemic viewpoint, in particular with a human resources perspective. We consider we have to make visible the human resources space as a key component of health sector reform, not only from a quantitative understanding, such as the need of medical specialists to provide health care, but also as the thinking block in the health system, so the quality, training, knowledge and expertise of these core resources, will be reflected in the quality of health sector reform proposals. Thus, we propose a dynamic flow among inception, implementation and deployment of health reform proposals, human resources development, and proposals development nuclei. This relationship is seen as a circular link, whereby balances and reinforcements in any of the three spaces determines changes in the other two; therefore, the proposed reform, there will be only feasible in áreas where there are available human resources.